The Impact of Peer Instruction on Academic Achievements and Creative Thinking Skills of College Students - Bulut, Birol (Eurasian Society of Educational Research, 2019)
In the context that it was scrutinized in the present study, peer instruction was initially developed by Eric Mazur, a physicist. The aim of the present study was to determine the impact of peer instruction method on academic achievements and creative thinking skills of the students. The study was conducted with the pre-test-posttest control group method, a quasi-experimental design, which was defined as a two-factor mixed design. The study was conducted with sophomore students attending Firat University (FU), Faculty of Education, Social Studies Teaching Department in Turkey during the 2018-2019 academic year spring semester. The experiment (N = 30) and control (N = 30) groups were determined with convenience sampling (a non-random sampling method). Present study findings demonstrated that peer instruction method improved the achievement and creative thinking skill levels of the students. However, it was observed that the method was more effective on course achievement. © 2019 The Author(s).
Keywords: academic achievements; creative thinking; Peer instruction